Basic biomechanics of the musculoskeletal system - Nordin, Margareta; Frankel, Victor H.; Leger, Dawn (Wolters Kluwer/Lippincott Williams & Wilkins, 2012)
Uses a direct and comprehensive approach to present students with a working knowledge of biomechanical principles of use in the evaluation and treatment of musculoskeletal dysfunction. This text opens with a chapter that introduces the basic terminology and concepts of biomechanics. It focuses on the biomechanics of tissues and structures